Advanced computational geometry for proximity queries of convex polyhedras - Sundaraj, Kenneth; Retnasamay, V. (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org